KONDISI KELUARGA KORBAN BANJIR DAN ANALISA KEBUTUHAN PELAYANAN SOSIAL DI JAKARTA BARAT Studi di Kelurahan Rawa Buaya - Kecamatan Cengkareng - Anwar Sitepu; Sugiyanto Sugiyanto (Politeknik Kesejahteraan Sosial, 2007)
As the floodwaters, which inundated Jakarta early have caused sorrows to many Jakarta,including in Rawa Buaya, Cengkareng, West Jakarta, have give rise to suffering for many people, like spread throughout the street, made unfit daily activities, and also caused damage for things and forced many people to leaved out from their home. Impacts for this situation, especially for poor and the poorest families in rural area. Their home was broken and loss many materials. This research purposed to assessment and identifies the social aid for the survivor’s floodwaters. Based on the problems, the survivors need aid for recovery they life, like home, material, etc. Beside the material, they social need therapy for social-psychology to handle traumatic situation and to raise self confidence and spirit for alive.Key Words : floodwaters, survivors